Detection of antibiotic resistance spectrum and resistance genes for aminoglycoside, macrolide, and β-lactam antibiotics using wound swab samples - Safain, Kazi Sarjana (Brac University, 2021)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2020.